Chemical and mineral characteristics, bioactive compounds and antioxidant activity of blackberries grown in an organic system - Souza, Rafaela Schmidt; Martins, Carlos Roberto; Antunes, Luis Eduardo Corrêa; Vizzotto, Márcia; Krolow, Ana Cristina Richter; Malgarim, Marcelo Barbosa (Comunicata Scientiae, 2020)
Blackberry bushes have increasingly drawn producers’ and consumers’ interest since they find their cultivation characteristics, production and nutraceutical qualities advantageous. Both chemical and mineral characteristics, bioactive compounds and antioxidant activity found in blackberries are extremely relevant factors to be considered when cultivars are chosen. Chemical analyses of the nutritional composition of fruit is important, since they can help studies of quality genotypes. Besides, fruit with high nutritional values contribute to human health when they are often consumed. This study aimed at evaluating chemical and mineral characteristics, besides bioactive compounds and antioxidant activity, of different blackberry bush genotypes grown in an organic farming system in Pelotas, Rio Grande do Sul (RS), Brazil. Production, soluble solid content, hydrogenionic potential, total titratable acidity, SS/TA ratio, minerals, phenolic compounds, anthocyanins and antioxidant activity of six blackberry bush genotypes – ‘Tupy’, ‘BRS Xingu’, Selection Black 178, Selection Black 128, Selection Black 112 and Selection Black 145 – were evaluated. It was a randomized block design with three replicates of every plant. Selection Black 178 yielded fruits with the highest value of SS/TA ratio and had the highest accumulated production. The highest anthocyanin content was found in ‘BRS Xingu’. Selection Black 112 had the highest total contents of phenolic compounds and the highest antioxidant activity, whereas ‘Tupy’ exhibited their lowest values. Selection Black 178 adapted well to the organic farming system, a fact that did not happen to Selection Black 128.